Biomodification of feedstock for quality-improved biochar: A green method to enhance the Cd sorption capacity of Miscanthus lutarioriparius-derived biochar. (20th May 2022) - Xu, Yi; Wu, Shenglan; Huang, Fengguang; Huang, Hongmei; Yi, Zili; Xue, Shuai
Abstract: Severe environmental and ecological problems have resulted due to the unharvested Miscanthus lutarioriparius biomass in Dongting Lake, the largest miscanthus production hub in the world. Pyrolyzing the miscanthus biomass to produce biochar is a win–win strategy for abandoned miscanthus biomass utilization and Cd-polluted paddy restoration in Hunan. However, the sorption efficiency of biochar requires improvement by modification. It is theoretically possible that biological modification by fungi and bacteria as well as a modification technique using Fe will increase the Cd sorption capacity. Thus, the current study used two biomass biomodification techniques, FB (fungal decomposition) and BB (bacterial digestion), and one biochar Fe-modification technique (by NH3 ·H2 O–FeCl3 ), and determined their ability to improve biochar quality. The results showed that the biomass modification by FB and BB increased the Cd sorption capacity of the derived biochar. The Cd sorption capacity of FB-derived biochar (36.4 mg g −1 ) was significantly greater as compared to BB-derived biochar (30.2 mg g −1 ) and the unmodified control (14.8 mg g −1 ). This improvement can be further optimized by Fe-modification, with an average potential of 22.2% (13.5–32.3%). The increased Cd sorption capacity is attributed to (in descending order of importance) the increased amount of ash, specific surface area, amount of alkaline functional groups and phenolic hydroxyl groups, and the pH of the biochar after modification. The Fe-FB-derived biochar pyrolyzed under 650 °C was tested and exhibited the highest Cd sorption capacity, at 64.9 mg g −1 . Biomodification of M. lutarioriparius biomass and its subsequent pyrolysis to produce biochar will simultaneously provide economic and ecological benefits. This approach provides a model for the integrated production of food and energy from biomass. Graphical abstract: Image 1 Highlights: Biomass modification strongly increases the Cd sorption capacity of biochar. Fungal decomposition and bacterial digestion are effective modification techniques. The Cd sorption capacity of biochar can be further optimized by Fe modification.